Twentieth-century short story explication. New series : with checklists of books and journals used - Walker, Warren S.; Aycock, Wendell M. (Hamden, Conn. : Shoe String Press, 1993)
Contains nearly <6000> entries that provide a bibliography of interpretations for short stories published between 1989 and <2000>.
Vols. 2-<6> by Wendell M. Aycock.
Vol. 5-<6> published in North Haven, Conn.
Includes bibliographical references and indexes.
Keywords: Short stories -- Indexes; Short stories -- Indexes